2012
DOI: 10.1007/s10725-012-9670-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fluorescent Pseudomonas spp. with single and multiple PGPR traits for plant growth promotion of sorghum in combination with AM fungi

Abstract: Traits involved in plant growth promotion by bacteria are ambiguously decided as phytohormones, siderophores, HCN, proteases, chitinases, cellulases, ammonia, exopolysaccharide production and phosphate solubilization or antagonistic activity. A total of 40 fluorescent Pseudomonas strains were isolated from diverse soils of various agro-ecosystems of India. Among these 7 strains viz, P1, P10, P13, P18, P21, P28 and P38 were selected depending on their character of possessing single or multiple PGPR traits. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 32 publications
(25 reference statements)
2
12
0
Order By: Relevance
“…The results indicated that the combined use of AM fungi and PB was a more effective treatment than the single use of either PB or AM fungus in affecting sorghum yield and quality. These results are similar to the results of Kumar et al (2012) who found that fluorescent Pseudomonas strains increased sorghum growth more efficiently in the presence of mycorrhizal fungi than in the absence of the fungi. Similar to our used bacterial features (Table 2), PGPR colonize plant roots and exert beneficial effects on plant growth and development by a wide variety of mechanisms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results indicated that the combined use of AM fungi and PB was a more effective treatment than the single use of either PB or AM fungus in affecting sorghum yield and quality. These results are similar to the results of Kumar et al (2012) who found that fluorescent Pseudomonas strains increased sorghum growth more efficiently in the presence of mycorrhizal fungi than in the absence of the fungi. Similar to our used bacterial features (Table 2), PGPR colonize plant roots and exert beneficial effects on plant growth and development by a wide variety of mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…Mycorrhization of wheat (Triticum aestivum L.) and maize (Zea mays L.) was not affected by different Azospirillum species or by a genetically modified derivative of Azospirillum brasilense overproducing indole-3-acetic acid, indicating the variations in AM fungi-PGPR interactions (Russo et al, 2005). Similar results were found by Kumar et al (2012). Crop quality including the rates of fibre, starch and proteins is an important aspect affecting the use and the efficiency of crop plants by the consumers.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…IAA, a member of phytohormone group, acts as important signal molecule in the regulation of plant growth (Kumar et al, 2012). In our study most of the Pseudomonas isolates were positive for IAA production (76%).…”
Section: Discussionsupporting
confidence: 53%
“…Bacillus and Pseudomonas were the main PGPR used in agricultural practice (Pandey et al, 2005;Niu et al, 2011). Pseudomonas could promote plant growth by facilitating phosphate solubilization or antagonistic activity or by producing phytohormones, siderophores and hydrogen cyanide (Kumar et al, 2012). Pseudomonas also could increase biomass (Gholami et al, 2009), enhance yield (Rosas et al, 2009) and relieve the damage of water stress (Sandhya et al, 2010) and drought stress (Kohler et al, 2009) to the plants.…”
Section: Effects Of Inoculation With Rhizobacteria On Root Respiratormentioning
confidence: 99%